Wounded attachments to disaster recovery: Gendered structural violence and everyday life, Indian experiences explored. (1st June 2021) - Joseph, Jacquleen; Jauhola, Marjaana; Arvind, Lavanya Shanbhogue; Gadavi, Shyam
Abstract: In this paper, we suggest that theorising on gendered structural violence and inequalities in disaster recovery would benefit from the in-depth focus on intersections of social relations and processes as they manifest in everyday lives. Drawing from the theorising on neoliberal states, we propose a new theoretical approach of "wounded attachments to disaster recovery". This theoretical position is informed by the lives of three women survivors from three diverse disasters in India. Five perspectives on gendered disaster recovery experience is then presented: firstly, how the recovery beneficiary categories are an extension of the neoliberal subject position; secondly, how recovery reinforces gendered responsibilities as "building oneself back better", a respectable mother and provider; thirdly, how recovery causes pain, suffering, and ressentiment; fourthly, how complex inequalities and social relations are lived through and negotiated in the aftermath of disasters; and finally, how women narrate counter cultural everydayness to disaster recovery in their life histories. We suggest that an understanding of intersectionality, or interlocking systems of oppression, as a form of injury, allows to understand power and structures of disaster recovery. Reiterations of such injuries suggest that instead of reducing vulnerability, and injustice, recovery efforts reiterate these very structures of inequality. The failure to operationalize and capture the complexities of structural inequality and injustice in the context of disaster recovery could be overcome by drawing on the work of scholars who recognise the limits of the concept of intersectionality and engage in alternate conceptualizations, such as pain, suffering, trauma and wounded attachments.